Investigação sobre aspectos de uso energético nos processos de soldagem a resistência por ponto para as versões corrente alternada (CA) e corrente contínua a média frequência (MFDC) - Rosa, Omar dos Santos (2013)
The resistance spot welding machines (RSW) are widely used by automobile industries. They are commercially available in two versions: alternating current (AC) and medium-frequency direct current (MFDC). In technical literature, it is possible to find comparative studies were with reference to button weld, spot geometry, mechanical strength and its formation in coated and uncoated steel plates. However, comparison between these machines, under the point of view of its energy use, still lacks. Thus, the aim of this work is to conduct a study on the energy efficiency of both AC and MFDC machines, splitting into three phases. The first one is the development of a mathematical model for each machine. Secondly, the two developed models were validated by using a factorial design 3k, where the selected factors were welding current and plate thickness. The observed responses were the effect on the primary current, which compared with the simulated current validated the mathematical models. The third phase deals with the analysis of the electrical efficiency by using a central composite design (PCC), where the factors were time, power, current and plate thickness, and observed responses were the energy efficiency and the weld button diameter. It is possible to conclude that the AC machine showed better performance compared to the MFDC machine, whose main purpose machines for resistance welding points.